1948
DOI: 10.1111/j.1467-6494.1948.tb01194.x
|View full text |Cite
|
Sign up to set email alerts
|

Learning in Schizophrenia

Abstract: As part of a study of schizophrenia (9) involving physiological, psychiatric, and psychological aspects, several expenments on learning were included The purpose of the study as a whole was to obtain a comprehensive structural picture of schizophrenia The psychological approach was organized to cover a number of functions from simple to complex levels Some of these already have been reported in detail or summary form (22) This paper is concerned with one of the learning experiments It compares pursuit learnmg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

1959
1959
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 23 publications
3
18
0
Order By: Relevance
“…Consistent with results from both the schizophrenia and the nonclinical psychosis literature, our results showed that compared with control individuals, UHR individuals performed more poorly on the pursuit rotor task (Gomar et al, 2011; Granholm, Bartzokis, Asarnow, & Marder, 1993; Huston & Shakow, 1948; Kern et al, 2010; Mittal, Dean, et al, 2012; Picard et al, 2008; Schwartz et al, 1996). In addition to poorer performance on the pursuit rotor task, UHR individuals in our study showed a slower rate of learning than did control individuals.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with results from both the schizophrenia and the nonclinical psychosis literature, our results showed that compared with control individuals, UHR individuals performed more poorly on the pursuit rotor task (Gomar et al, 2011; Granholm, Bartzokis, Asarnow, & Marder, 1993; Huston & Shakow, 1948; Kern et al, 2010; Mittal, Dean, et al, 2012; Picard et al, 2008; Schwartz et al, 1996). In addition to poorer performance on the pursuit rotor task, UHR individuals in our study showed a slower rate of learning than did control individuals.…”
Section: Discussionsupporting
confidence: 90%
“…1 for an anatomical map of these regions), may be important for the storage of internal models related to motor function and, thus, responsible for learning (Manni & Petrosini, 2004; Marr, 1969; Schlerf, Verstynen, Ivry, & Spencer, 2010; Stoodley & Schmahmann, 2009, 2010). There is evidence to suggest procedural learning impairment in UHR individuals: Recent work has demonstrated deficits in pursuit rotor performance in individuals exhibiting nonclinical psychosis (otherwise healthy individuals who report at least one fleeting subclinical psychotic-like experience per year), and several studies have indicated similar deficits in patients with formal psychosis (Gomar et al, 2011; Huston & Shakow, 1948; Kern, Hartzell, Izaguirre, & Hamilton, 2010; Mittal, Dean, & Pelletier, 2012; Scherer, Stip, Paquet, & Bedard, 2003; Schwartz, Rosse, Veazey, & Deutsch, 1996). …”
mentioning
confidence: 99%
“…The study of reheating is beyond the scope of this work -preliminary results suggest that isocurvature perturbations do, in fact, decay during the reheating phase. 74 However, this is very much an open question, and will be the subject of future work.…”
Section: Isocurvature Perturbations In Multi-field Inflationary Modelsmentioning
confidence: 99%
“…On all of these tasks, schizophrenia patients were impaired even before antipsychotic drugs were available (Huston and Shakow, 1948). The basis of impaired procedural learning on manual but not oculomotor skills remains to be clarified.…”
Section: Effects Of Risperidone On Procedural Learning Msh Harris Et Almentioning
confidence: 99%